Long-term drying trend during 51.8–37.5 Ma in the Nangqian Basin, central-eastern Qinghai–Tibet Plateau - Li, Shangkun; Ma, Xueyun; Jiang, Shaohua; Wang, Gen; Zhang, Ting; He, Wei; Yu, Xiaoli; Ma, He; Zhang, Pengyuan; Wei, Jingyi; Wang, Yongli; Wei, Zhifu (Frontiers in Earth Science, 2022)
According to the indexes of organic geochemistry , the source of organic matter and the evolution of paleoclimate and paleo-vegetation in Nangqian basin since 51.8~37.5 Ma can be divided into three stages: stage I: 51.8~46.4 Ma BP, the climate is humid in all, the vegetation type was mainly aquatic herbaceous plants, the sources of organic matter were mainly submerged / floating aquatic plants, and the input of lower organisms such as aquatic bacteria and algae was less. Stage Ⅱ: 45.0~42.7 Ma BP, the climatic conditions gradually drought, accompanied by periodic drought and wet changes; the vegetation type changed from woody plants to herbaceous plants, the source of organic matter mainly changed from submerged / floating aquatic plants to terrestrial higher plants, and the input of lower organisms such as aquatic bacteria and algae was less. Stage III: 42.7 ~37.5 Ma, the climatic conditions continued to dry, which may be affected by MECO events, and the content of organic matter increased obviously; the vegetation type was mainly herbaceous plants; the source of organic matter is mainly the mixed input of submerged / floating aquatic macroplants and terrestrial higher plants, and the input of lower organisms such as aquatic bacteria and algae is less. Through the comparative study of the climate evolution history of the Eocene in the Nangqian Basin reconstructed by the multi-index system with the climate change in the adjacent area, the retreat process of the Paratethys Sea, the global deep-sea oxygen isotopes and the global atmospheric CO2 concentration, it is considered that the Eocene climate change in the Nangqian Basin is mainly affected by the global climate change and the retreat of the proto-Paratethys Sea. The uplift of the Qinghai-Tibet Plateau and the increase of altitude have a little influence on the water vapor in the Nangqian Basin,while the basin was less affected by the South Asian monsoon.